Students’ Responses toward Lecturer’s Corrective Feedback on Writing 3 at English Teaching Learning Program of IAIN Madura - Lina Suhartina Puteri; Siti Azizah (PANYONARA: Journal of English Education, 2022)
Writing is one of the skills in language learning requiring some abilities to be conducted. The students should pass some steps in writing. They sometimes do not know what the steps exactly are to be done first in order that they can begin writing well. The lecturer corrected the students’ writing as feedback based on the errors or mistakes made by the students. So, the corrective feedback given by the lecturer can be various. Every lecturer’s corrective feedback is expected to make the students understand what errors are made and what they should do with those errors. Here, the students’ responses can be seen. The purposes of this study are to know how the students respond to the lecturer’s corrective feedback and what styles of response shown by the students. The researcher conducted this study was qualitative descriptive research method. Interview and documentation were conducted and used by the researcher to collect the data from the lecturer and students. To check the validity of the data, the researcher used the triangulation method. The results of this research show that some students respond to the lecturer’s corrective feedback differently and the sudents’ response styles used by the students are obedient students, dependent students, and independent students.